Pengaruh Besarnya Ultrafiltrasi terhadap Perubahan Tekanan Darah pada Pasien PGK di Unit Hemodialisa RSUD Kabupaten Tangerang - Sulastri Sulastri; Zahrah Maulidia Septimar; Lastri Mei Winarni (Jurnal Health Sains, 2021)
The magnitude of ultrafiltration is the process of transferring dissolved substances and water due to hydrostatic differences in blood and dialysate which are carried out from the patient's body weight. The purpose of this research is of the amount of ultrafiltration on changes in blood pressure in clients with chronic kidney disease at Tangerang Regional Hospital. Methods: This study used a quasi-experimental design with a one group study, the population of all patients in the hemodialysis room, a sample of 150 people. Results: The study showed that the amount of ultrfiltration both experienced changes in normal BP was 17 respondents (50.1%), respondents with a moderate amount of ultrafiltration were experiencing a change in low BP, the most were 2 respondents (66.6%) and the number of respondents, the amount of ultrafiltration, was multiplying changes in high BP, around 42 respondents. (37.2%). Chi Square test obtained an Asymp.Sig. (2-sided) value of 0.035 <0.05, there is an influence between the amount of ultrafiltration on changes in blood pressure in CKD patients at the HD Unit of the Tangerang District Hospital 2020. Conclusion to improve hemodialysis services with restrictions and Monitoring the amount of ultrafiltration can minimize the risk of a drop in blood pressure that can endanger the patient's life.